Radiotherapy with or without temozolomide in elderly patients aged ≥ 70 years with glioblastoma - Metcalfe, Evrim; Karaoglanoglu, Ozden; Akyazici, Emine (Contemporary Oncology/Współczesna Onkologia, 2016)
Introduction : Although the recommended optimal treatment of glioblastoma multiforme (GBM) is adjuvant chemoradiotherapy, trials in GBM have excluded patients older than 70 years. In this study, we aimed to assess overall survival (OS) and prognostic factors in elderly patients (≥ 70 years) with newly diagnosed GBM treated with radiotherapy (RT) ± concurrent/adjuvant temozolomide (TMZ). Material and methods : Inclusion criteria were patients ≥ 70 years, pre-RT Karnofsky performance status (KPS) ≥ 60, and time between diagnosis and start of RT ≤ 2 months. A total of 40 patients aged ≥ 70 years, 12 female and 28 male, treated between January 2004 and December 2012, were evaluated. Median age was 73.5 years (range, 70–83 years). The median RT dose was 60 Gy (range, 30–62 Gy). Twenty-one (52.5%) received concurrent TMZ, and of those 12 (30%) went on to receive adjuvant TMZ. Results: The median OS was 7 mon- ths (95% CI: 5.45–8.54). One- and two-year OS for the whole cohort was 38% and 16%, respectively. Sex, type of surgery, tumor size, and RT dose did not significantly affect the OS. Presence of concurrent TMZ (p < 0.005) and presence of adjuvant TMZ (p < 0.001) were associated with longer OS in our cohort. Conclusions : RT ± TMZ seems to be a well-tolerated treatment in patients ≥ 70 years with GBM. Even though no superiority was found between conventional or hypofractionated RT regimens (p = 0.405), the addition of concurrent and adjuvant TMZ to RT increased the OS in our study.